2004
DOI: 10.1002/macp.200300033
|View full text |Cite
|
Sign up to set email alerts
|

Photosulfonation of Low‐Density Polyethylene Films

Abstract: Summary: Photosulfonation of low‐density polyethylene (LDPE) films by UV irradiation in the presence of gaseous sulfur dioxide (SO2) and oxygen (O2) was studied by attenuated total reflectance (ATR) infrared spectroscopy and X‐ray photoelectron spectroscopy (XPS). The ATR and XPS analysis and chemical modification of UV‐irradiated LDPE films demonstrated the generation of CC double bonds and sultones in the reaction. These results indicated the possibility that sulfur trioxide (SO3) was produced during the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Different studies have been performed on the surface sulfonation of polyethylene lm using oleum and chlorosulfonic acid. [10][11][12][13][14] Likewise, the inherent hydrophilicity of poly vinyl alcohol (PVA) makes it an attractive polymer for water treatment application, where adequate cross-linking ensures compaction under pressure. 15 In some of the previous works, different cross-linking agents have been used to serve this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have been performed on the surface sulfonation of polyethylene lm using oleum and chlorosulfonic acid. [10][11][12][13][14] Likewise, the inherent hydrophilicity of poly vinyl alcohol (PVA) makes it an attractive polymer for water treatment application, where adequate cross-linking ensures compaction under pressure. 15 In some of the previous works, different cross-linking agents have been used to serve this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…have also been shown to alter membrane properties. [19][20][21][22][23] It has been reported that membrane alone contributes to more than 38% of the overall cost in MFC. 24 Another apt way of enhancing membrane efficiency is usage of inorganic llers as nanocomposite membranes.…”
Section: Introductionmentioning
confidence: 99%
“…16 Various studies on enhancing membranes properties have been conducted; for instance, surface modication of polyolens by sulfonation, photosulfonation, plasma treatment, and radiation graing have been shown to improve hydrophilicity, adhesion, and other properties within membrane. [17][18][19][20][21] Recently, polyvinylidene uoride (PVdF) and its blends have provided a promising prospective as PEM in fuel cell technology. [22][23][24][25][26][27][28] Although, being hydrophobic, various studies on its surface modication have shown increments in water retention capability within the membranes.…”
Section: Introductionmentioning
confidence: 99%